Art and the Challenge of Markets Volume 1 National Cultural Politics and the Challenges of Marketization and Globalization (Sociology of the Arts ,, 2018)
Art and the Challenge of Markets Volumes 1 & 2 examine the politics of art and culture in light of the profound changes that have taken place in the world order since the 1980s and 1990s. The contributors explore how in these two decades, the neoliberal or market-based model of capitalism started to spread from the economic realm to other areas of society. As a result, many aspects of contemporary Western societies increasingly function in the same way as the private enterprise sector under traditional market capitalism. The first volume of this two-volume collection considers a broad range of national cultural policies from European and North American countries, and examines the strengthening of international and transnational art worlds in music, visual arts, film, and television. The chapters cover cultural policy and political culture in the United States, United Kingdom, Germany, France, Switzerland, the Nordic countries, the Balkans, and Slovenia, and address the extent to which Western nations have shifted from welfare-state to market-based ideologies. Tensions between centres and peripheries in global art worlds are considered, as well as complex interactions between nations and international and transnational art worlds, and regional variations in the audiovisual market. Both volumes provide students and scholars across a range of disciplines with an incisive, comparative overview of the politics of art and culture and national, international and transnational art worlds in contemporary capitalism.